IMPLEMENTASI SISTEM JARINGAN INFORMASI BERSAMA ANTAR SEKOLAH DI SMAN 1 BATUSANGKAR KABUPATEN TANAH DATAR - Afriyanti Dwi Kartika; Jefril Rahmadoni; Hafizah Hanim; Ricky Akbar; Fajril Akbar; Ullya Mega Wahyuni; Husnil Kamil (Jurnal Hilirisasi IPTEKS, 2022)
Senior High School 1 Batusangkar is a public school that has utilized technology in the implementation of school activities, starting from the presence of a website as an information room, using computers and the internet at school. In addition, this school is also equipped with four computer laboratories which are used for teaching rooms for students. However, in daily activities, the data generated by the school has not been integrated into an information system properly. This has become a momentum for the Department of Information Systems, UNAND in assisting schools in implementing, socializing and educating the school information system JIBAS (Inter-School Information Network) at Senior High School 1 Batusangkar as a tangible form of carrying out the Tri Dharma of Higher Education, namely community service. JIBAS is a school management information system that helps school operations ranging from academics, finance, libraries, reporting and teacher-student interactions. It is hoped that this system can help schools organize, manage and tidy up their data. Thus, this data becomes information that flows and is useful for various interested parties. The implementation method for this activity consists of three stages, namely preparation, implementation, and evaluation. After this community service activity was carried out, the school felt that this system was very good to be developed and used further for school activities as a whole. However, with the various other features that exist in JIBAS besides the Academic features, the school needs to study other features so that the effectiveness and efficiency presented by this system can be felt by the school..